Imperceptibility and robustness analysis of DWT-based digital image watermarking - Yusof, Yusnita; Khalifa, Othman Omran (2008)
Digital watermarking is distinctive depending on the techniques used and its intended applications. This paper concentrates on invisible digital image watermarking using discrete wavelet transform. The work flow involves watermark embedding, attacks and watermark extraction. Two methods are proposed and analyzed to imply the imperceptibility and robustness, among the most important criteria of digital watermarking, using three types of attacks – JPEG compression, blurring and histogram equalization. The results are compared through subjective visual inspections and calculative measurements using PSNR for watermark imperceptibility and SSIM Index for watermark robustness.